Pelatihan Manajemen Sampah Berbasis Rumah Tangga melalui Penerapan Mini Komposter pada Kelompok PKK di Bantul - Afraah, Sayyidah Maulidatul; Sofyandi, Muhammad Saddam; Mulyani, Maulidia; Ramadhan, Galih Dwi; Sajiwo, Bagus; Bakti, Gagas Nusa; Ahmadi, Win Fauzi; Rofiah, Siti; Nurjannah, Sianani; Wegayanti, Intan Ayu Nur (Journal of Appropriate Technology for Community Services, 2025)
In 2023, the waste production in D.I. Yogyakarta Province reached 440,267.76 tons per year, with household waste contributing the largest portion at 44.3% of the total. The continuous rise in waste is attributed to the increasing population and declining quality of life. Additionally, the local community's lack of awareness about effective waste management, such as composting food waste, exacerbates the problem, making it difficult for them to handle the waste they generate. This initiative aimed to educate the Padukuhan Sawit community, particularly RT.002, on household-based waste management practices. It included discussions and hands-on training on how to use mini composters. The methodology involved a field survey, discussions with community leaders, preparation and planning, socialization, distribution of mini composters, and an evaluation and demonstration of the proper use of mini composters. The program, conducted over two sessions, garnered significant enthusiasm from the participants. Out of the 10 mini composters distributed, only 4 were used independently. The main barrier preventing wider adoption was the fear of failure, such as unpleasant odors or other technical issues. Therefore, there is a need for strategic follow-up and mentoring to ensure the sustainability of the initiative. Such as monitoring each representative of the dasa wisma and distributing spare EM4 fluid to facilitate waste management for other residents.